Abdominal Epilepsy, A Diagnosis to Consider in Children with Recurrent Vomiting: A Case Report - Fatia Murni Chamida; Nirmala Muflihatul Khalida (Ikatan Dokter Indonesia Wilayah Jawa Timur, 2023)
gastrointestinal complaints and central nervous system involvement, mainly confusion, fatigue, headache, dizziness, syncope, and lethargy resulting during the abdominal seizure activity. Chronic vomitting or other gastrointestinal symptoms often lead to fluid and nutritional deficiencies which resulted in malnutrition. To date, there was no study has been reported on abdominal epilepsy in Indonesia. Case Presentation: We presented a case of two-year-old girl with chief complaint of recurrent profuse vomiting every month for the past year. Patient complained of headaches and abdominal pain and tended to sleep all day during relapse. Physical examination showed sunken eyes and decreased skin turgor. EEG showed abnormal results, diffuse irritative, epileptiform with normal basic rhythm. Esophageal polyps were also found on endoscopy. Patient was given anti-epileptic drugs and histamine H2 receptor antagonists and responded well to those therapies. Conclusion: Abdominal epilepsy is a rare case which may resulted in vomiting and abdominal pain in children. EEG examination is an important test for diagnosing abdominal epilepsy. Treatment with anti-epileptic drugs is known to respond well in this case.